1998
DOI: 10.1002/(sici)1099-0992(199805/06)28:3<383::aid-ejsp870>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

On the (dis-)confirmability of stereotypic attributes

Abstract: Two experiments investigated the linguistic abstractness and confirmability of elements contained in ingroup and outgroup stereotypes. The first experiment shows that positive elements of the ingroup stereotype (Italians) and negative elements of the outgroup stereotype (Jews, Germans) tended to be particularly abstract. Also, negative elements contained in the outgroup stereotypes required relatively little evidence to be considered ‘true’ but much disconfirming evidence to be rejected as ‘false’. No such bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This analysis would entail not only a manipulation of active and passive voice but the removal of agents in the passive voice altogether (Lafrance & Hahn, 1994;Lamb, 1991). Moreover, when coupled with a manipulation of verb type (Maass et al, 1998;Semin & Fiedler, 1991), this approach could provide a powerful experimental analysis of the role of language in persuasion in English. Of course, the field would also benefit from an analysis of linguistic masking in languages other than English.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis would entail not only a manipulation of active and passive voice but the removal of agents in the passive voice altogether (Lafrance & Hahn, 1994;Lamb, 1991). Moreover, when coupled with a manipulation of verb type (Maass et al, 1998;Semin & Fiedler, 1991), this approach could provide a powerful experimental analysis of the role of language in persuasion in English. Of course, the field would also benefit from an analysis of linguistic masking in languages other than English.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive indictment runs through the professional literature: The prejudiced are too quick to jump to conclusions about target groups, too slow to acknowledge disconfirming evidence and to update beliefs in response to such information, and prone to see relationships between variables and group membership that are weakly or not at all connected (Allport & Postman, 1947;Henderson-King & Nisbett, 1996;Huici, Ros, Carmona, Cano, & Morales, 1996;Maass, Montalcini, & Biciotti, 1998;Rothbart, Evans, & Fulero, 1979;Rothbart & John, 1985;Ybarra, Schaberg, & Keiper, 1999;Ybarra, Stephan, & Schaberg, 2000). The moral indictment is no less explicit.…”
Section: Is It Possible To Pass Classic Correspondence and Coherence mentioning
confidence: 99%
“…In support of this idea, previous research has shown that stereotypes tend to take the form of abstract trait expectations such as 'Women are sensitive' or 'Men are dominant'. For example, Maass, Montalcini, and Biciotti (1998) asked research participants to generate a list of characteristics that they thought were typical of different social groups ( Jews, Italians, Germans). Despite the fact that participants had explicitly been told that they could either use phrases (hence verbs) or adjectives, adjectives clearly prevailed over any other linguistic form.…”
Section: Ida and Stereotypesmentioning
confidence: 99%